2018
DOI: 10.1002/clc.23053
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale of the atrial fibrillation occurring transiently with stress (AFOTS) follow‐up cohort study

Abstract: Atrial fibrillation occurring transiently with stress (AFOTS) describes the first detection of AF in a patient who is hospitalized for a non-cardiac medical illness or following non-cardiac surgery. Uncertainty exists whether episodes of AFOTS are due to reversible precipitants and will not recur after recovery, or if they are paroxysmal atrial fibrillation (AF) that is detected during inpatient cardiac monitoring. Previous studies have used retrospective, non-systematic and ultimately low-sensitivity protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Similarly, this study was not designed to assess the association of AF with inhospital outcomes. Finally, the study was also not designed to assess long-term outcomes, although some participants were coenrolled into our ongoing AFOTS follow-up study ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study was not designed to assess the association of AF with inhospital outcomes. Finally, the study was also not designed to assess long-term outcomes, although some participants were coenrolled into our ongoing AFOTS follow-up study ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a large proportion of patients with postoperative AF may have recurrent AF episodes detected in the months and years after their index hospitalization, 14,[22][23][24] and an ongoing prospective study is addressing rates of AF recurrence. 25 If perioperative AF is the first episode or first presentation of paroxysmal AF, then these patients may have an increased long-term risk of stroke and death. No systematic evaluation of the data of the long-term risks of stroke and death in patients with new-onset perioperative AF after noncardiac surgery is available.…”
mentioning
confidence: 99%
“…Our detection rate of 34% over 30 days of self-monitoring, is similar to the detection rate of 30% noted in a recent study that used an event recorder for ~14-days during months 1-, 6-, and 12 following discharge after surgery for malignancy [17] . To date, we are not aware of any other prospective studies that have reported on secondary AF recurrence after discharge, although a Canadian study is in progress [18] . Our previous study that employed similar methodology to the current study using a handheld ECG following cardiac surgery, identified an AF recurrence rate of 24% within 17-days of discharge [14] .…”
Section: Discussionmentioning
confidence: 99%